Risk Factors of Donor Site Seroma Formation and Laboratory Analysis of Seromas after Breast Reconstruction with a Latissimus Dorsi Flap - Seongwon Lee (Archives of Aesthetic Plastic Surgery, 2018)
Background Donor site seroma is the most frequent and troublesome complication of latissimus dorsi (LP) flaps. This study aimed to identify the risk factors of seroma formation after an LD flap and to evaluate the biochemical composition of seromas. Methods The medical records of 84 patients who underwent an LD flap from September 2007 to May 2017 were reviewed. Age; body mass index (BMI); the type of breast surgery, reconstruction, and nodal dissection; the usage of fibrin glue; smoking; chemotherapy; and history of diabetes mellitus or hypertension were evaluated. In 11 of the 84 patients, the levels of electrolytes, glucose, proteins, lipids, and inflammatory markers present in seromas were investigated. Results The overall incidence of seroma was 66.7%. Advanced age (≥45 years) and overweight (BMI ≥23 kg/m2) were significant risk factors for seroma. Patients who underwent an extended LD flap had a higher incidence of seroma than those who underwent a standard LD flap, while those who underwent breast-conserving surgery had a lower incidence of seroma than those who underwent other breast procedures. Lactate dehydrogenase (LDH) levels in seromas on postoperative day 2 demonstrated a positive linear correlation with the duration of drainage, but this relationship did not reach statistical significance. Conclusions Advanced age, overweight, wider excision or mastectomy, and use of an extended LD flap were found to be risk factors for seroma formation after breast reconstruction with an LD flap. It may be possible to infer whether a seroma will be long-lasting by measuring LDH levels in the seroma.